Patterns Of Social Interaction Between Different Ethnic Groups In Malaysian Secondary Schools - Mohd Yusof, Najeemah (Penerbit Universiti Sains Malaysia, 2006)
Social interaction among students of different ethnic groups has been a major focus of study in Malaysia in recent years. Schools in Malaysia have students from a variety of ethnic, linguistic, religious and cultural backgrounds. When students of a variety of backgrounds are put under one roof, there is a strong tendency to differentiate and polarize. This article will discuss the patterns of social interaction amongst students of different ethnic groups in secondary schools. A research was conducted in 15 secondary schools in Kedah and Pulau Pinang with 581 students as samples. The nature of social interaction in this study is classified according to several factors such as ethnicity, sex or gender, academic achievement, school level and the student's former primary school (feeder school) before they enrolled in the secondary school. The students were given a set of questionnaires and findings were analysed quantitatively. The findings show that students prefer to mix with others in their own ethnic group.